INDONESIAN GRADUATE STUDENTS’ STRATEGIES IN REGULATING THEIR MOTIVATION IN ACADEMIC READING - Ayu Mahardika, Agustine Andriana; Kuswandono, Paulus (Premise: Journal of English Education and Applied Linguistics, 2022)
Self-regulation is required to retain or even improve the students’ motivation to achieve the targeted goal. Students can arrange, observe, and assess their learning and thinking processes. In the process of reading, students might find difficulties that can make them unmotivated, and they need better motivation-regulation to help them attain their motivation to achieve the targeted goal. Therefore, it can be understood that motivation is a key factor to help the students’ strategies in regulating their motivation in academic reading. Nineteen graduate students of the English Education Master’s Program (EEMP) of Sanata Dharma University batch 2021 were the participants in this research. One research question to be answered in this research is “what are the strategies undertaken by graduate students’ in regulating their motivation in academic reading?” Mixed-method was implemented to answer the research question and discover nineteen graduate students’ strategies in regulating their motivation in academic reading. The data were gathered using questionnaires and interview instruments. The result revealed that the students used some motivation-regulation strategies to boost and maintain their motivation in reading academic journals namely interest enhancement, goal-oriented self-talk, self-consequating, and environmental control. This research also has implications for the students, thesis advisors, and future researchers.